circEPS15 Overexpression in Hepatocellular Carcinoma Modulates Tumor Invasion and Migration - Jiang, Bin; Tian, Maolin; Li, Gang; Sadula, Abuduhaibaier; Xiu, Dianrong; Yuan, Chunhui; Bing, Yuntao (Frontiers in Genetics, 2022)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths worldwide. Recent evidence has shown that circular RNAs (circRNAs) play important roles in tissue development, gene transcription, signal regulation and tumorigenesis. However, whether circRNAs are involved in HCC progression and encode functional proteins remains largely unknown. In the present study, we aimed to explore the function and molecular mechanism of circRNAs in HCC. First, many circRNAs were found to be differentially expressed in HCC samples and paired adjacent normal liver tissues. The validation of dysregulated circRNAs by qRT-PCR revealed that circEPS15 expression was downregulated in HCC tissues, and the survival curves showed that low circEPS15 levels were associated with poor overall survival in HCC patients. Then, the overexpression of circEPS15 suppressed tumor cell invasion and migration by inhibiting the TJP1/CDH2/VIM signaling pathway and retarded cell cycle progression, which was confirmed by the Transwell culture system, wound healing assays, flow cytometry and western blot assays. After that, the spanning junction open reading frame in circEPS15 driven by IRES was shown to encode a novel protein, which was verified by western blotting with full-length, mutated, and truncated sequences of circEPS15 with a FLAG tag. Moreover, ceRNA analysis and qRT-PCR results suggest a possible circRNA (circEPS15)-miRNA-mRNA network in HCC. Collectively, our study reveals that endogenous circEPS15 plays a novel role in repressing HCC through the ceRNA network and encodes a functional protein.